2020
DOI: 10.1111/1751-7915.13506
|View full text |Cite
|
Sign up to set email alerts
|

Co‐cultivation of Thermoanaerobacter strains with a methanogenic partner enhances glycerol conversion

Abstract: Glycerol-rich waste streams produced by the biodiesel, bioethanol and oleochemical industries can be treated and valorized by anaerobic microbial communities to produce methane. As current knowledge of the microorganisms involved in thermophilic glycerol conversion to methane is scarce, thermophilic glycerol-degrading methanogenic communities were enriched. A co-culture of Thermoanaerobacter and Methanothermobacter species was obtained, pointing to a non-obligately syntrophic glycerol degradation. This hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For the quantification of lactic acid and SCFA, an HPLC system equipped with an Aminex HPX-87H chromatographic column (8 µm, 30 cm × 0.46 cm length × diameter) coupled with a UV detector (wavelength: 210 nm) was used. Samples were eluted in a solution of sulfuric acid (5 mM) at a 0.7 mL/min flow rate and 60 °C [ 30 ]. The chromatographic signal was recorded and further integrated using the Star Chromatography Workstation 6.3 software (Varian, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the quantification of lactic acid and SCFA, an HPLC system equipped with an Aminex HPX-87H chromatographic column (8 µm, 30 cm × 0.46 cm length × diameter) coupled with a UV detector (wavelength: 210 nm) was used. Samples were eluted in a solution of sulfuric acid (5 mM) at a 0.7 mL/min flow rate and 60 °C [ 30 ]. The chromatographic signal was recorded and further integrated using the Star Chromatography Workstation 6.3 software (Varian, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Syntrophic relationships between fermentative bacteria (e.g., Thermoanaerobacter species, Escherichia coli ) and methanogens were reported to facilitate glycerol fermentation (Magalhães et al 2020 ; Richter and Gescher 2014 ; Zhang et al 2015 ). However, co-culture Gly-M incubated with BrES was not able to degrade glycerol, nor to produce methane (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other bacteria can oxidize glycerol coupled to the reduction of external electron acceptors, such as sulfate (Clomburg and Gonzalez 2013 ), or in syntrophy with hydrogenotrophic methanogens (Qatibi et al 1991a , b ). Syntrophic collaboration was even shown to accelerate glycerol degradation (Magalhães et al 2020 ; Richter and Gescher 2014 ), possibly because it facilitates the maintenance of the proper intracellular redox balance. Zhang et al ( 2015 ) suggested that the use of mixed cultures for glycerol degradation may present economic and process advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Their presence in GP digestion could be explained considering the high concentration of promptly digestible lipids (7-15%) and proteins (8-16%) that characterized this substrate (43). In fact, in A. hydrogeniformans genome a thermostable esterase was identi ed presenting high catalytic activity with a preference towards short-acyl-chain esters (44), while A.thermoterrenum is involved in glycerol conversion (45), both processes being related to lipids metabolism during AD. Moreover, is interesting to notice that both strains of Acetomicrobium observed in this study potentially act as syntrophic partner with homoacetogenic or syntrophic acetate-oxidizing bacteria (SAOB)(46), and with acetoclastic or hydrogenotrophic methanogens (HM) even if their role in these syntrophic communities still remains enigmatic (47).…”
Section: Dynamics Of Microbial Community In Ad Process Grape Pomacementioning
confidence: 99%